Optical 3-D Metric Measurements of Local Vocal Fold Deformation Characteristics in an In Vitro Setup - Hüttner, Björn; Sutor, Alexander; Luegmair, Georg; Rupitsch, Stefan; Lerch, Reinhard; Döllinger, Michael (IEEE Transactions on Biomedical Engineering, 2011)
Understanding vocal fold dynamics presents an essential part in treating voice disorders as it is the prerequisite to appropriate medical therapy. Various physical and numerical models exist for simulation purposes, all relying on simplified material parameters. To improve current approaches, data of realistic tissue behavior, i.e., in natural surroundings, have to be considered in model development. An in vitro setup was proposed for tensile tests combined with an optical method for precise, local and metrical 3-D measurements of distinctive surface points. Compared to previous 3-D reconstruction methods, the accuracy was improved tenfold. Vertically applied forces versus resulting deformation were measured for ten porcine vocal folds. Deformation characteristics of mucosa and the two-layer structure of mucosa and muscle (MM) were investigated at three distinctive locations along the vocal fold edge. The spring rates were represented by an exponential function. For equal deflections, an increasing spring rate from posterior to anterior for MM was measured. For solely mucosa, the spring rate decreased from the posterior to the middle and subsequently increased again. The MM-layer presented a stiffer deformation behavior than mucosa. For deformations higher than 1.5 mm, the spring rates for MM were more than twice as high as for mucosa. The investigations display the importance of considering both multilayers and local differences for the improvement of vocal fold models.
Keywords: Image processing; optical measurement; stereo triangulation; tensile test; vocal fold deformation characteristics